Use of Beds in The Event of a Scabies Infection in Boarding Schools - Tjatur Sembodo; Hesti Wahyuningsih Karyadini; Yusti Nur Aisyah Sanna (Universitas Airlangga, 2021)
Background: Research on scabies in boarding schools has been widely carried out, however, the nature of transmission has not yet been analyzed. The transmission can occur due to the risk of direct contact when using shared beds. Purpose: This study aims to analyze the risk of bed usage in the event of a scabies infection in boarding schools. Methods: This study adopted a case-control design method. The independent variable was the use of beds, including using a shared bed and using one's own bed. The dependent variable was scabies, which was determined on the basis of the diagnostic criteria set for scabies. The sample size was 60 students, who had lived for at least four weeks in boarding schools. The sample comprised two groups: the group that used a shared bed (30 students) and the group that used their own beds (30 students). A non-probability sampling method was employed to record data. The data was collected by using a scabies checklist. Direct examinations and interviews were conducted at the Fathul Huda Demak and the Selamat Kendal boarding schools in February 2020. Statistical tests were carried out using chi-square analysis. Results: This study revealed the risk of developing scabies when a shared bed was used, with p=0.00 (p<0.05); OR=7.67; and 95%CI= 2.42–24.25. Conclusion: Students who used a shared bed in boarding schools were at 7.67 times the risk of developing scabies compared to students who used their own beds.